Going Round in Circles: Mobility, Destination and Experience - Clarke, Alan (TeMA - Journal of Land Use, Mobility and Environment, 2011)
This paper addresses the changing approaches to transport in urban tourism as seen through the move from functional sectoral accounts towards a perspective informed by the experience economy. By reviewing the traditional service offers, it is possible to unpack what lies within the service dominant logics that lead to co-creation of value and the realisation of quality tourism experiences. The paper then considers the adoption and adaptation of traditional forms of transport within the value proposition in urban tourism. Mobility in tourism is a strangely new focus of attention, strangely because without it there would be no tourism to speak of. However mobility requires a framework of civil and legal entitlements that allow people to move and a transport infrastructure that allows those rights to be realised in both working and leisure time situations. This article will address the construction of the tourism transport infrastructure by examining the ways in which the transportation elements in mobility have been re-thought within tourism. The first part of the paper will re-construct an account of transport and mobility which deals with it in terms of the functions and logistics of delivery, both between points of origin and destinations, and within destinations. These perspectives can be seen in the texts which shape the basic tourism curriculum (Cooper et al, 2008; Page, 2009) and explain how tourism and transport have developed over the years by integrating the opportunities provided by the new technologies – motorised vehicles (both cars and coaches), trains, ships and aeroplanes – to allow for the development of a range of destinations. Lumsdon and Page (2004) introduced a new approach to transport and tourism by distinguishing between transport for tourism and transport as tourism, which provides a linkage between the first and second parts of this article. The second part will develop an account of mobility in tourism that demonstrates how their uniqueness derives from what the ‘Service-dominant (S-D) logic’ (Vargo and Lush, 2004; Vargo and Morgan, 2005; Vargo and Lush 2006) would call value co-creation. Hyde and Laesser (2008) emphasised the important role of transport in the tourist decision-making process associated with destination choice behaviour but it is necessary to move beyond this construction of the interconnections (Andersson, 2007). These elements of transport were generally considered to be “goods” or “products” including both tangible and intangible factors. Physical goods become one element among others in a total service offering, from an exhibition to a living performance or a concert and transportation has become an integral part of that experience if not of the offer.